2020
DOI: 10.3389/fcimb.2020.00412
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Short Chain Fatty Acids to the Growth of Pseudomonas aeruginosa in Rhinosinusitis

Abstract: Background: Chronic rhinosinusitis (CRS) is characterized by complex bacterial infections with persistent inflammation. Based on our rabbit model of sinusitis, blockage of sinus ostia generated a shift in microbiota to a predominance of mucin degrading microbes (MDM) with acute inflammation at 2 weeks. This was followed by conversion to chronic sinus inflammation at 3 months with a robust increase in pathogenic bacteria (e.g., Pseudomonas). MDMs are known to produce acid metabolites [short chain fatty acids (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…SCFAs could inhibit cytokines and nitric oxide production by monocytes/macrophages and not improve the survival of pulmonary-sepsis ( Ciarlo et al., 2016 ). Furthermore, recent studies found that excessive SCFAs have detrimental effects on the host ( Zumbrun et al., 2013 ; Cho et al., 2020 ). It has been reported that a high-fiber diet (producing more SCFAs) promotes pathogenic Escherichia coli O157:H7 strain colonization and increases mortality ( Zumbrun et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SCFAs could inhibit cytokines and nitric oxide production by monocytes/macrophages and not improve the survival of pulmonary-sepsis ( Ciarlo et al., 2016 ). Furthermore, recent studies found that excessive SCFAs have detrimental effects on the host ( Zumbrun et al., 2013 ; Cho et al., 2020 ). It has been reported that a high-fiber diet (producing more SCFAs) promotes pathogenic Escherichia coli O157:H7 strain colonization and increases mortality ( Zumbrun et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SCFAs, especially acetic acid, could also promote the proliferation of PA. The high concentration of acetic acid in sinusitis mucus was a risk factor for chronic rhinosinusitis with PA infection ( Cho et al., 2020 ). On the other hand, some clinical studies also found that SCFAs may be detrimental ( Kurilshikov et al., 2019 ; Behary et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Placing Merocel packing (Medtronic, Inc, Minneapolis, MN) inside the rabbits' nasal cavity is challenging due to (1) the size of the nasal cavity (especially for nonrhinologists) and (2) handling the rabbits (monitoring vital signs) under sedation, both of which have an associated learning curve. Also, the thick pathologic mucus seems to drive inflammation in the sinus mucosa, 4 and, if all thick pathologic mucus is suctioned out initially when removing the Merocel, then chronic sinusitis may not develop thereafter. We are curious about the reinduction criteria for the 6 rabbits in the subset of this study.…”
Section: A Preclinical Model To Tackle Chronic Rhinosinusitismentioning
confidence: 99%